2013
DOI: 10.1590/s0103-84782013000200023
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do óleo de eucalipto (Corymbia citriodora) no controle do carrapato bovino

Abstract: Efeito do óleo de eucalipto (Corymbia citriodora) no controle do carrapato bovino.Ciência Rural, v.43, n.2, fev, 2013. Ciência Rural, Santa Maria, v.43, n.2, p.331-337, fev, 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
4
0
7
Order By: Relevance
“…A study conducted by Chagas et al (2002) demonstrated that essential oil of eucalypt exerted an important acaricide effect, as well as it had higher repellent and insecticide effects on Culex pipiens and Musca domestica (Batish et al, 2008). According to Olivo et al (2013), the use of essential oil of eucalypt has some limitations, such as low aqueous solubility, volatilization and instability, in different conditions. Thus, nanotechnology can be considered an interesting approach in order to provide protective effect on the active principle and, consequently, potentiating its effects.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Chagas et al (2002) demonstrated that essential oil of eucalypt exerted an important acaricide effect, as well as it had higher repellent and insecticide effects on Culex pipiens and Musca domestica (Batish et al, 2008). According to Olivo et al (2013), the use of essential oil of eucalypt has some limitations, such as low aqueous solubility, volatilization and instability, in different conditions. Thus, nanotechnology can be considered an interesting approach in order to provide protective effect on the active principle and, consequently, potentiating its effects.…”
Section: Introductionmentioning
confidence: 99%
“…Holstein cows bathed with 4.0 l of a solution of 3.5% eucalyptus essential oil (Corymba citriodora) presented an average efficacy of 69.2%, but it was superior than 90% on the 14 th and th days after the bath, which means greater efficacy on younger tick instars, such as larvae and nymphs. A sensory test was performed to evaluate if the applied solution transferred taste of eucalyptus to milk and derivatives (yoghurt): consumers of milk and yoghurt from treated animals did not notice altered taste or odour in the milk, nor was there an adverse effect to the animals (Olivo et al 2013). Interestingly, modifications in the citronellal molecule did not produce positive results in vivo (Chagas et al 2014).…”
Section: Natural Products For Treating Cattlementioning
confidence: 99%
“…Análise de regressão polinomial quadrática com os parâmetros de eficiência do tratamento e concentração de óleo de manjericão (Ocimum basilicum L.) (%) em teleóginas de Rhipicephalus (Boophilus) microplus.Diversos autores avaliando o efeito do óleo essencial, obtido de folhas de Ocimum suave, sobre larvas e adultos do carrapato Rhipicephalus appendiculatus, constataram que o óleo possui ação repelente e é tóxico para esta espécie (MWANGI et al 1995), com esta mesma planta Del Fabro e Nazzi (2008) apontaram para uma ação repelente sobre o carrapato Idoxes ricinus. Muitos outros autores avaliaram óleos essenciais e compostos isolados de plantas do gênero Ocimum e constataram que estes fitoterápicos possuem ação inseticida e acaricida (MURUGAN; MURUGAN;NOORTHEN, 2007, KOSTIC et al, 2008 DEL FABRO; NAZZI, 2008), como repelente(PADILHA et al, 2004), na ação na inibição do desenvolvimento e esporulação de fungos fitopatogênicos (SCHWAN-ESTRADA; STANGARLI;CRUZ, 2000), no desenvolvimento micelial de fungos(PEREIRA et al, 2006).Estudos com o óleo essencial de distintas espécies de eucalipto chegaram a 100% de eficácia(CHAGAS et al, 2002; AGNOLIN, 2012;OLIVO et al, 2013). Olivo et al (2009) verificaram que formulações contendo extrato aquoso de Nicotiana tabacum obtido por decocção, apresentaram um controle parcial do carrapato em bovinos naturalmente infestados.…”
unclassified